Strategi Desain Mengubah Lahan Parkir Mall Menjadi Sebuah Kafe Bertema Warehouse - Gabriele Nydia Njotohardjo; Gervasius Herry Purwoko; Rani Prihatmanti (Universitas Ciputra Surabaya, 2015)
The application of the customized handicraft in accordance with the needs of users will strengthen the interior of a room both commercial area and private area. The community desire to have private business in accordance with the development of the trend is there to be one of the establishment of GABs interior as a service company of the interior consultant that handle the area of public and private with application customized handicraft on each design as its value added.The application of customized handicraft which are succulent wall panels and artistic wall decor will be done to Rest-Art Cafe as thematic cafe with the theme of the warehouse. The election of furniture and interior accessories are also making the visitors look like being in the warehouse. Cafe is also equipped with open kitchen area that make visitors can watch the making of molecular gastronomy dessert that is become the excellence of this cafe